It's Rare So Be Aware: Pleuropulmonary Blastoma Mimicking Congenital Pulmonary Airway Malformation - Haider, Fayza; Al Saad, Khulood; Al-Hashimi, Fatima; Al-Hashimi, Hakima (The Thoracic and Cardiovascular Surgeon Reports, 2017)
Pleuropulmonary blastoma (PPB) is a rare aggressive malignant tumor of infancy and early childhood. The tumor arises in the lung and pleura and is regarded as a pulmonary dysontogenetic or embryonic neoplasm. Four types are defined in literature. Type I PPB is a rare, cystic lung neoplasm in infants characterized by subtle malignant changes and a good prognosis. Recurrences after type I PPB are usually advanced with a poor prognosis.We report this case to increase awareness about this entity so that the pediatricians, pediatric surgeons, radiologist, and pathologist recognize it early.
Keywords: Pleuropulmonary Blastoma; lung; benign or congenital lesions; airway (includes related subject matter); infant; pediatric